Kinematics and Workspace Analysis of 4-SPRR-SPR 5-DOF Parallel Mechanism - Guo Qiang Cui Guohua Zhang Fan Yu Haidong Cheng Zhenyi (Jixie chuandong)
Taking a 2T3R 5-DOF 4-SPRR-SPR parallel mechanism with rotating axis as the moving platform as the research object, the degree of freedom of the 4-SPRR-SPR parallel mechanism is analyzed by the screw theory, the inverse kinematics equation of the parallel mechanism is established by the vector method, the constraint of the pair of motion is analyzed in detail, and the workspace of the mechanism is obtained by the three-dimensional boundary search method. The results show that the workspace of the mechanism has the advantages of symmetry, no holes in the interior, regular cross-section shape, etc. At the same time, taking the workspace volume as the optimization objective, the influence curves of the constraints of the motion pair and the workspace volume are obtained, and the maximum factors affecting the workspace are obtained, it is the movement range of branch chain moving pair. The mechanism has good application prospects in cutting and grinding parts of complex space surface.